2018
DOI: 10.3390/pharmaceutics10030157
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Taste-Masking Techniques for Traditional Chinese Medicines

Abstract: A variety of pharmacologically active substances, including chemotherapeutic drugs and the substances from traditional Chinese medicine (TCM), always exhibit potent bioactivities after oral administration. However, their unpleasant taste (such as bitterness) and/or odor always decrease patient compliance and thus compromise their curative efficacies in clinical application. Therefore, the developments of taste-masking techniques are of great significance in improving their organoleptic properties. However, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 81 publications
(92 reference statements)
0
31
0
Order By: Relevance
“…As the oral administration is the most accepted route, masking the unpleasant taste of drugs to an acceptable degree of palatability is important during formulation. Masking techniques can be integrated into three levels: 1) formulation level, through sweeteners and flavors; 2) particle level, by creating a physical barrier between the bitter component and the taste receptors; and 3) molecular level, through the complexation of the drug with CDs or ion-exchange resins [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…As the oral administration is the most accepted route, masking the unpleasant taste of drugs to an acceptable degree of palatability is important during formulation. Masking techniques can be integrated into three levels: 1) formulation level, through sweeteners and flavors; 2) particle level, by creating a physical barrier between the bitter component and the taste receptors; and 3) molecular level, through the complexation of the drug with CDs or ion-exchange resins [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, VOC was brownish yellow oil and had extremely pungent smell, while VOC-β-CD had almost no pungent smell for people in our lab. Literatures showed that the inclusion complex not only effectively enhanced the dissolution of drugs in aqueous solutions, but also showed the potential to mask its bitter taste in the oral cavity [ 4 , 29 , 30 , 42 , 48 ]. VOC-P188 had a faint yellow appearance and still had pungent smell.…”
Section: Resultsmentioning
confidence: 99%
“…Sucrose and maltodextrin in granules have two functions: sweeteners and fillers. [20][21][22][23][24] Based on the organoleptic test results, it can be concluded that the processed functional beverage granules complied with the predetermined specifications. The functional beverage granules prepared from the combined extracts of guava © 2021 the authors.…”
Section: Resultsmentioning
confidence: 99%